Validation of cadaver-based trauma surgery training for lifelong skill development - Soichi Murakami; Toshiaki Shichinohe; Yo Kurashima; Kazufumi Okada; Yusuke Tsunetoshi; Ryoji Iizuka; Wataru Ishii; Kenji Kandori; Shinichiro Irabu; Naoki Shinyama; Hiroshi Homma; Masahiko Watanabe; et al. (World Journal of Emergency Surgery)
Abstract Background The decline in trauma cases and the increase in non-surgical treatments have reduced opportunities for trauma surgery training. This study examined the effectiveness of Cadaver-Based Educational Seminar for Trauma Surgery (C-BEST) as a lifelong educational tool for novice and experienced clinicians. Methods From 2017 to 2023, 117 clinicians with varying levels of experience participated in the C-BEST program at Hokkaido University. Participants included novice clinicians (median years post-graduation: 5) and experienced clinicians (median years post-graduation: 19). Each participant assessed their confidence in 21 trauma techniques before, immediately after, and 6 months post-course using a self-assessment of confidence levels (SACL) scale. Results The analysis showed significant improvement in SACL scores immediately after the course, with confidence levels remaining sustained 6 months later. Novice clinicians demonstrated substantial skill acquisition, whereas experienced clinicians reported the reinforcement and refinement of existing skills. Conclusions C-BEST seems valuable as a training tool for the acquisition and retention of trauma surgery skills, addressing practical needs in trauma care. C-BEST provides an effective and sustained approach to trauma surgery skill development and retention across career stages. Further research on its long-term impact and applicability in diverse clinical settings is recommended.